Transformation Of Local Values In Sustainable Development Policies: A Rural Sociology Perspective - Loso Judijanto; Tran Thi Lan; Andrei Popescu (Yayasan Adra Karima Hubbi, 2025)
Background. Local values embedded within rural communities often play a decisive role in shaping attitudes toward environmental stewardship, social cohesion, and economic resilience. In the context of sustainable development, the integration of these values into formal policies remains a complex challenge due to tensions between traditional norms and modern governance frameworks. Purpose. This study aims to analyze the transformation of local values in the formulation and implementation of sustainable development policies, adopting a rural sociology perspective to understand the interplay between culture, social structures, and policy processes. Method. A qualitative research design was employed, combining in-depth interviews with community leaders, policy-makers, and local residents, along with document analysis of regional development plans. Data were collected from three rural districts undergoing active policy reforms aimed at balancing economic growth with environmental sustainability. Results. Findings indicate that local values are not merely preserved or discarded but often reinterpreted to align with broader development goals, resulting in hybrid governance practices. This transformation is influenced by political negotiation, generational shifts, and external pressures such as globalization and climate change. Conclusion. The study concludes that sustainable development policies achieve greater legitimacy and long-term effectiveness when they are co-created with communities, ensuring that local values are adapted without losing their core identity.